2022
DOI: 10.1038/s41598-022-09306-6
|View full text |Cite
|
Sign up to set email alerts
|

Human liver organoid derived intra-hepatic bile duct cells support SARS-CoV-2 infection and replication

Abstract: Although the main route of infection for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the respiratory tract, liver injury is also commonly seen in many patients, as evidenced by deranged parenchymal liver enzymes. Furthermore, the severity of liver damage has been shown to correlate with higher mortality. Overall, the mechanism behind the liver injury remains unclear. We showed in this study that intra-hepatic bile duct cells could be grown using a human liver organoid platform. The cholangi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…The severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2), the causative pathogen for the coronavirus disease 2019 (COVID-19) has caused an ongoing pandemic since its first appearance end of December 2019. Although the main symptoms of COVID-19 are of respiratory nature, ranging from mild flu-like symptoms to severe pneumonia causing acute respiratory distress syndrome (ARDS) and multi-organ failure, there are emerging reports on a wide range of extrapulmonary systemic symptoms, including hepatic and biliary complications [1][2][3]. Liver injury has been observed in a significant proportion of patients ranging from 16 to 45%, especially in those with a severe or critical illness and prolonged stay at the intensive care unit (ICU) [4].…”
Section: Introductionmentioning
confidence: 99%
“…The severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2), the causative pathogen for the coronavirus disease 2019 (COVID-19) has caused an ongoing pandemic since its first appearance end of December 2019. Although the main symptoms of COVID-19 are of respiratory nature, ranging from mild flu-like symptoms to severe pneumonia causing acute respiratory distress syndrome (ARDS) and multi-organ failure, there are emerging reports on a wide range of extrapulmonary systemic symptoms, including hepatic and biliary complications [1][2][3]. Liver injury has been observed in a significant proportion of patients ranging from 16 to 45%, especially in those with a severe or critical illness and prolonged stay at the intensive care unit (ICU) [4].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have demonstrated that human bile duct organoids are susceptible to SARS-CoV-2 and support viral replication. [ 72 , 73 ] Furthermore, primary hepatocytes and cholangiocytes in culture and organoids infected with SARS-CoV-2 overexpress pro-inflammatory cytokines and downregulate metabolic processes, [ 64 ] raising the possibility that infection may alter the profile of pro-inflammatory or pro-fibrogenic cytokines. Additionally, there may be impairment of bile transport and bile acid signaling, in part from downregulation of bile acid transporters and chloride channels.…”
Section: Mechanisms Of Gastrointestinal and Hepatobiliary Injurymentioning
confidence: 99%
“…Furthermore, it was recently shown that SARS‐CoV‐2 is able to infect and replicate in organoids derived from human intrahepatic biliary epithelial cells (BECs). [ 5 ] While histopathological studies have reported detection of SARS‐CoV‐2 RNA and/or proteins in human liver tissue and bile samples, [ 6 ] it remains elusive whether SARS‐CoV‐2 replicates in BECs in vivo . Presuming cytopathic effects on the hepatobiliary system, the route of SARS‐CoV‐2 infection of the liver is unknown, but it could be blood‐borne because viral RNA and virions were detected in patients with severe disease.…”
Section: Case Report/study Number Of Patients (N) Metabolic Risk Fact...mentioning
confidence: 99%